PENGEMBANGAN CROSSWORD PUZZLE PENGEMBANGAN CROSSWORD PUZZLE MELALUI PROBLEM BASED LEARNING PADA MATERI PETA INDONESIA UNTUK MENINGKATKAN BERPIKIR KRITIS SISWA KELAS V UPT SD NEGRI MINGGIRSARI KABUPATEN BLITAR: PENGEMBANGAN CROSSWORD PUZZLE MELALUI PROBLEM BASED LEARNING - M. Chafidh Tamami; Mohamad Fatih; Shofi Nur Amalia (Journal of Practice Learning and Educational Development, 2026)
This study sought to create a crossword-puzzle teaching aid using a problem-based learning approach on the Indonesian map topic to enhance fifth graders’ critical thinking at UPT SD Negeri Minggirsari, Blitar RegencyThe ADDIE paradigm, This was applied in the research and development design and includes analysis, design, development, implementation, and assessment. The product's fitness for usage was indicated by validation ratings of 81.2% from a subject-matter expert and 92.5% from a media expert. A pretest total of 1,020 and a posttest total of 1,853 were obtained by testing the product with 20 students, resulting in an N-gain of 0.84 (high). As a result, the problem-based crossword puzzle helped students develop their critical thinking skills about the Indonesian map.